Analysis of Vitamine C Levels in Rice Snail Mucus (Pila ampullacea) - Nurul Ilma Septiani; Elsa Yuniarti; Helendra Helendra; Yusni Atifah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Rice snails are one of the pests that have the potential to cause high losses to rice plants. Rice snail mucus contains glycosaminoglycans, proteoglycans, glycoprotein enzymes, copper peptides, metal ions, collagen, elastin, glycolic acid, allantoin, antimicrobial peptides and vitamin C. Vitamin C or ascorbic acid is one of the vitamins needed by the body that functions as a help process in the body's metabolism. To determine vitamin C levels can be done using the UV-VIS spectrophotometry method with a wavelength of 260 nm. This study aims to determine vitamin C levels from rice snail mucus concentration of 100% and rice snail mucus concentration of 50%. This study is descriptive quantitative, analyzing vitamin C levels obtained from a spectrophotometer can be seen from the absorbance of rice snail mucus. Based on the results of research obtained from the analysis of vitamin C levels of rice snail mucus, the concentration of 100% is 2,372. While vitamin C levels in rice snail mucus concentration of 50% were obtained at 0.911. So it can be concluded that there are vitamin C levels in rice snail mucus with a concentration of 100% greater absorbance than 50% rice snail mucus.